194k views
5 votes
How to solve 2x^2-3x-1=0

User JimmyNJ
by
5.1k points

1 Answer

3 votes

\begin{gathered} x_1=(-9+√(17))/(2) \\ x_2=(-9-√(17))/(2) \end{gathered}

Step-by-step explanation


2x^2-3x-1=0

Step 1

remember the quadratic formula.

if you have the equation


ax^2+bx+c=0

the value for x is


x=(-b^2+√(b^2)-4ac)/(2a)

Step 2

let


ax^2+bx+c=2x^2-3x-1

a=2

b=-3

c=-1

Step 3

replace


undefined

User Jemlifathi
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.